2012
DOI: 10.1073/pnas.1113960109
|View full text |Cite
|
Sign up to set email alerts
|

CD24 expression is important in male urothelial tumorigenesis and metastasis in mice and is androgen regulated

Abstract: Overexpression of CD24, a glycosyl phosphatidylinositol-linked sialoglycoprotein, is associated with poor outcome in urothelial carcinoma and contributes to experimental tumor growth and metastasis. However, the requirement for CD24 ( Cd24a in mice) in tumorigenesis and spontaneous metastasis from the orthotopic site remains uncharacterized. Using N -butyl- N -(4-hydroxybutyl) nitrosamine induction of invasive and metastatic bladder cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
90
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(93 citation statements)
references
References 45 publications
2
90
1
Order By: Relevance
“…CD24, a RAL GTPase-regulated glycosyl phosphatidylinositol (GPI)-linked sialoglycoprotein, is required for metastatic bladder cancer colonisation in mice and shows increased expression in human bladder cancer metastases 183 . Interestingly, prognostic value seems to be confined to male patients and in Cd24-null mice, reduced carcinogen-induced tumour incidence was seen only in males 184 . As CD24 is androgen-responsive, if these data are confirmed, androgen ablation could have therapeutic impact in males 184 .…”
Section: Emt and Metastasismentioning
confidence: 99%
See 1 more Smart Citation
“…CD24, a RAL GTPase-regulated glycosyl phosphatidylinositol (GPI)-linked sialoglycoprotein, is required for metastatic bladder cancer colonisation in mice and shows increased expression in human bladder cancer metastases 183 . Interestingly, prognostic value seems to be confined to male patients and in Cd24-null mice, reduced carcinogen-induced tumour incidence was seen only in males 184 . As CD24 is androgen-responsive, if these data are confirmed, androgen ablation could have therapeutic impact in males 184 .…”
Section: Emt and Metastasismentioning
confidence: 99%
“…Interestingly, prognostic value seems to be confined to male patients and in Cd24-null mice, reduced carcinogen-induced tumour incidence was seen only in males 184 . As CD24 is androgen-responsive, if these data are confirmed, androgen ablation could have therapeutic impact in males 184 .…”
Section: Emt and Metastasismentioning
confidence: 99%
“…Ablation of CD24 resulted in fewer metastases than in control animals. Interestingly, this result was restricted to male mice, suggesting a role for androgens (Overdevest et al 2012). In cell culture studies, an AR knockdown resulted in decreased CD24 expression and cell proliferation, while treatment with androgens increased CD24 levels, arguing that CD24 is androgen regulated in urothelial cells (Overdevest et al 2012).…”
Section: The Role Of the Ar In Bladder Cancer Invasion And Angiogenesismentioning
confidence: 87%
“…Interestingly, this result was restricted to male mice, suggesting a role for androgens (Overdevest et al 2012). In cell culture studies, an AR knockdown resulted in decreased CD24 expression and cell proliferation, while treatment with androgens increased CD24 levels, arguing that CD24 is androgen regulated in urothelial cells (Overdevest et al 2012). Others have found that androgen stimulation of AR positive bladder cancer cells promoted a mesenchymal phenotype, migration and invasion in vitro, and metastasis in vivo (Jing et al 2014).…”
Section: The Role Of the Ar In Bladder Cancer Invasion And Angiogenesismentioning
confidence: 91%
“…Macrophage in tumors, generally known as tumor-associated macrophage (TAMS), are often upregulated urethra. Since the BBN model only produces tumors in male mice, 34 direct instillation of AuNPs into the bladders of male mice is challenging, but could be done surgically. Further, transitional human bladder tumors could be injected into in the stromal compartment of solid tumors and participate in their growth, angiogenesis, and metastasis.…”
Section: Discussionmentioning
confidence: 99%